BIM-based framework to analyze the effect of natural ventilation on thermal comfort and energy performance in buildings. (February 2019) - Gan, Vincent J.L.; Deng, M.; Tan, Y.; Chen, W.; Cheng, Jack C.P.
Abstract: Buildings use significant amount of energy worldwide, with mechanical air-conditioning systems accounting for a large proportion of the total energy consumed. Utilizing natural ventilation can achieve a comfortable indoor thermal environment while reducing the use of air-conditioning and building energy consumption. However, previous studies mainly focused on either thermal comfort or energy conservation by utilizing natural ventilation. The correlation between thermal comfort and energy performance due to the effect of natural ventilation is important, but has not been studied thoroughly in literature. Moreover, natural ventilation in buildings is greatly affected by building geometry, material property, outdoor environmental condition and occupancy, which were not fully incorporated in the previous studies. This paper presents a framework based on building information modeling (BIM) to study the effect of natural ventilation on the correlation between thermal comfort and energy performance. BIM provides 3D building models with detailed geometric and material information as well as the building location and type that help determine the outdoor environmental condition and occupancy, thereby improving the accuracy of natural ventilation simulation. A case study was conducted using the proposed framework, aimed at investigating the natural ventilation in a residential flat in Hong Kong at different seasons. The results show that utilizing natural ventilation cannot always achieve thermal comfort. Natural ventilation brings cool air in late spring (April) during which the indoor temperature can be controlled at a comfortable level and the energy use for mechanical ventilation can be saved. The proposed framework helps evaluate the natural ventilation in buildings for maintaining indoor thermal comfort at minimal energy use, thereby creating a more sustainable built environment.